Projeto Meraki - Silva, Marcelo Formigoni da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
We realize this days a spacing of individuals, on what concerns their relationships with others. At the same time, the technologies and the possibilities of virtual interaction are more and more present and developed. At this point, we draw a connection between the virtual immersion and the detachment from personal and face to face relationships. Wear this reality, this project proposes a discussion of the communications while transmitting messages and content, as well as a basis for social relations developed between individuals in a given society. From this analysis, we depart for the development of an action joining the Public Relations and Design, while communication areas that when involved, enable the development of an empirical theory for the increased use of social relations, through the feelings

Percebemos nos dias de hoje um afastamento dos indivíduos no que condiz aos seus relacionamentos com terceiros. Ao mesmo tempo, as tecnologias e as possibilidades de interação virtual se mostram mais e mais presentes e desenvolvidas. Nesse ponto, traça-se uma ligação entre a imersão no virtual e o desapego das relações pessoais e presenciais. Visto essa realidade, o presente projeto propõe uma discussão acerca do universo da comunicação enquanto transmissora de mensagens e conteúdos, bem como base para as relações sociais desenvolvidas entre os indivíduos de uma determinada sociedade. A partir dessa análise, partiremos para o desenvolvimento de uma ação que una as Relações Públicas e o Design, enquanto áreas comunicacionais que, envolvidas, possibilitam o desenvolvimento de uma teoria empírica para o maior uso das relações sociais, através dos sentimentos
Keywords: Comunicação - Aspectos sociais; Desenho industrial; Relações publicas; Emoções; Communication - Social aspects